2009
DOI: 10.1002/ibd.20860
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of Escherichia coli in the human gut: New ecological evidence supporting the role of adherent-invasive E. coli (AIEC) in Crohnʼs disease

Abstract: New data about ecological parameters of AIEC reinforces the implication of AIEC in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
320
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 348 publications
(345 citation statements)
references
References 48 publications
12
320
4
1
Order By: Relevance
“…Most E. coli strains isolated from the ileal mucosa of CD patients are able to adhere to and invade intestinal epithelial cells (14)(15)(16) and belong to the pathogenic group of adherent invasive E. coli (AIEC) (17). AIEC is highly associated with the ileal mucosa in CD patients (14)(15)(16)(18)(19)(20)(21)(22)(23). CD-associated AIEC cells adhere to the brush border of primary ileal enterocytes isolated from CD patients but not to enterocytes isolated from controls without inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Most E. coli strains isolated from the ileal mucosa of CD patients are able to adhere to and invade intestinal epithelial cells (14)(15)(16) and belong to the pathogenic group of adherent invasive E. coli (AIEC) (17). AIEC is highly associated with the ileal mucosa in CD patients (14)(15)(16)(18)(19)(20)(21)(22)(23). CD-associated AIEC cells adhere to the brush border of primary ileal enterocytes isolated from CD patients but not to enterocytes isolated from controls without inflammatory bowel disease.…”
mentioning
confidence: 99%
“…18 Increased levels of E. coli and AIEC strains have been repeatedly observed in ileal CD patients, suggesting a role for E. coli in disease pathogenesis. [19][20][21] In earlier work from our laboratory, we found that patients with ileal CD have a mucosal microbiome enriched for MDX metabolism, as compared to colonic CD patients and non-IBD controls. 22 Additionally, we demonstrated that MDX has a direct effect on multiple E. coli strains, including AIEC, to enhance cellular adhesion and biofilm formation, mimicking the dense biofilms observed in the gut of CD patients 21 (Fig.…”
Section: Maltodextrin (Mdx) Is a Common Food Additive That Alters Botmentioning
confidence: 99%
“…Indeed recent genomic studies have failed to identify any AIEC-specific genes that can adequately explain the ability of this group of E. coli to invade epithelial cells and replicate in macrophages (Clarke et al, 2011;Krause et al, 2011;Miquel et al, 2010;Nash et al, 2010;Vejborg et al, 2011;Zhang et al, 2015). Nonetheless epidemiological evidence does suggest that E. coli are enriched in the guts and macrophages of the lamina propria of CD patients compared to healthy controls (Conte et al, 2014;Darfeuille-Michaud et al, 2004;de Souza et al, 2012;Elliott et al, 2015;Martinez-Medina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%